Gastrointestinal physiology (Mosby, 2001)
This book is the market leader in its field. This concise, readable text provides basic concepts and information related to gastrointestinal physiology. The material is presented in a format that makes it easily understandable for anyone learning GI physiology. This New Edition is updated with additional clinical information, two-color illustrations, summaries, bold-faced key terms, and end-of-chapter review questions, as well as a mini-exam at the end of the book.